2020
DOI: 10.1021/acsaem.0c00711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Degradation Mechanisms in Slot-Die-Coated Nonfullerene ITO-Free Organic Solar Cells Using Different Illumination Spectra

Abstract: We compare pristine and degraded samples that were subjected to outdoor degradation following standard ISOS-O2 protocol. The ideality factors for different incident wavelengths obtained from open circuit voltage versus irradiation level and current density-voltage (J-V) measurements at different temperatures, indicate that for aged samples recombination is governed by Shockley-Red-Hall mechanism occurring in a region near the anode. Samples were also characterized using impedance spectroscopy and fitted to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The antioxidants are relevant as industrial processing always allows for inclusion of small amounts of oxygen in the cell during fabrication (done in air), which even the best encapsulant cannot protect against. Transport layer interface degradation is also well-known, in particular for many new non-fullerene based organic solar cell systems [236,237], for example due to photocatalytic decomposition of these molecules at metal oxide interfaces. This has made studies on transport layer interfaces very relevant for the OPV field [238].…”
Section: Pv Generators For Iotmentioning
confidence: 99%
“…The antioxidants are relevant as industrial processing always allows for inclusion of small amounts of oxygen in the cell during fabrication (done in air), which even the best encapsulant cannot protect against. Transport layer interface degradation is also well-known, in particular for many new non-fullerene based organic solar cell systems [236,237], for example due to photocatalytic decomposition of these molecules at metal oxide interfaces. This has made studies on transport layer interfaces very relevant for the OPV field [238].…”
Section: Pv Generators For Iotmentioning
confidence: 99%
“…Consequently, ITIC exhibits much stronger degradation under UV light compared to the visible light region. In addition to the UV light, Arredondo et al [64] also used two monochromatic illuminations (λ = 630 and 450 nm) to study the photon stability of PBDB-T:ITIC system upon red or blue incident light. They found that although blue light can penetrate deeper in the sample while red light is mainly absorbed near the anode, the incident red light at 630 nm caused significant degradation in the photoactive layer.…”
Section: (8 Of 23)mentioning
confidence: 99%
“…The introduction (or doping) of various materials, such as perylene bisimides, fullerene derivatives, aluminum, and different two-dimensional (2D) materials, into ZnO electron transport layers have been reported, yielding, e.g., improved conductivity and electron extraction properties and thus enhancing the overall device performance. A main drawback is the photocatalytic activity of ZnO, which in particular for several nonfullerene acceptor molecules has shown to lead to photodegradation of the active layer molecules and thus significantly hamper the device lifetime. In recent years, MXenes, a young class of 2D transition metal carbides and nitrides consisting of the general formula M n +1 X n T x , where M indicates a transition metal, X indicates C and/or N, and T x indicates terminal groups such as −OH, −F, O, or −Cl, have been extensively explored, as MXenes exhibit high electrical conductivity, high transmittance, as well as good chemical stability. Moreover, MXenes exhibit versatile surface chemistry, and the opportunities of tailoring their surface characteristics and work functions has triggered huge attention for the perovskite and OSC fields. …”
Section: Introductionmentioning
confidence: 99%